Belle's discovery - Roehl, Tessa; Disney Storybook Artists (New York : Random House, 2017)
"Young Belle has trouble fitting in at school until she discovers a neglected bookstore in the village and shows her classmates how wonderful books and stories can be"--
Keywords: JUVENILE FICTION / Media Tie-In.